Characteristics of Professional Formation’s Indicators of Managers of the System of the Ministry of Internal Affairs of Ukraine - Yu. Yu. Boiko-Buzyl (Law and Safety)
The problem of professional and personal formation of managers of the security and defense sector of Ukraine has been studied. It has been emphasized that the basis for professional and personal development of the managers of the Ministry of Internal Affairs of Ukraine is formed by the activity and personality as basic categories, which are reflected in the block of professional formation and the block of personal formation, where each block is reflected in specific components and is revealed in appropriate criteria. In particular, the first part of the study – the psychological characteristics of the block of professional development is presented, namely through such components and their criteria as: activity – career motivation, professional aspirations; behavior – a metasystem of relations in the activity, conflict resolution competence; work – managerial identity of the manager, managerial decision as a product, communication – socio-psychological competence, emotional and volitional regulation. The study is based on the use of a number of methods of psychological diagnosis, which assisted to examine 844 people, including 385 managers and 459 employees of the agencies and departments of the Ministry of Internal Affairs of Ukraine. The obtained results have been processed by using the methods of mathematical statistics. The originality of the stu